M1/M2 macrophages: origin, phenotype, methods of production, interaction with natural killer cells and trophoblast - A. S. Zhguleva; M. S. Zementova; S. A. Selkov; D. I. Sokolov (Медицинская иммунология)
This review presents current data on the origin of monocytes/macrophages, the conditions necessary for the differentiation of monocytes into M1 or M2 macrophages. Three subpopulations of peripheral blood monocytes are described: (I) classical – the main subpopulation (85-90%), effectively carrying out phagocytosis; (II) intermediate monocytes (5-10%) – participate in antigen processing and presentation, in angiogenesis, vascular endothelium restoration; (III) non-classical monocytes (10%) - "patrol" vascular network, remove cellular debris, participate in tissue remodeling. The review provides detailed characteristics for each subclass of macrophages: pro-inflammatory (M1) and anti-inflammatory (M2), which play different roles in the initiation and resolution of inflammation; their phenotype, the spectrum of secreted cytokines, the expression of transcription factors, and the functions performed are described. For the M2 population, the features of the subpopulation are described in detail: M2a, M2b, M2c, M2d. The review presents methods and approaches to obtaining polarized macrophages in vitro from both peripheral blood monocytes and cells of transplanted cultures based on signals received by macrophages in vivo; the phenotype, cytokine production and functional properties of artificially polarized macrophages depending on the conditions of their production are given. The review examines in detail the features of contact and distant interaction of macrophages of various subclasses with microenvironment cells on the example of natural killer cells and trophoblast cells, provides information on changes in the phenotype, transcriptional and secretory profile of interacting cells. The mechanisms of trophoblast control of macrophage differentiation into a unique M2 population of decidual macrophages controlling both the development and functioning of the trophoblast and its apoptosis are described. The review examines in detail the currently known variants of the interaction of macrophage subpopulations with natural killers. The influence of Mf on NK cells manifests itself in a change in the expression of transcription factors by the latter, which determine not only their differentiation, but also their functional activity. Macrophages are considered as cells that actively influence the functional state and differentiation of natural killers. The review examines the mechanisms of the relationship of all three types of cells: macrophages, trophoblast and natural killers in the area of uteroplacental contact. The study of the interactions of these cells will shed light not only on the features of intercellular relationships in the area of uteroplacental contact, but also on the relationship of tumor cells with NK cells and macrophages.